International terminology as an integration of different cultures into global science - Konarbayeva, Aliya T.; Aidarbek, Karlygash Zh.; Vollmann, Ralf; Smanova, Gaziza I. (Opción)
The study aims to investigate international terminology as an integration of different cultures into global science via comparative qualitative research methods. As a result, language structure cannot be studied without taking into account the nature of language use. This perspective is what characterizes argumentative discourse as a functional rather than a formal approach to language. In conclusion, the investigation of international terminology could help facilitate knowledge communication.